Green Economy Index Development as a Measurement Instrument for Green Economy Transition in Bogor Regency - Aidha Zulaika; Tjahjo Tri Hartono; Yuggo Afrianto; Immas Nurhayati; Ratna Pratini; Tazkialaras (Jurnal Rekayasa Lingkungan dan Biosistem, 2025)
This study develops and implements the Green Economy Index (GEI) as an instrument for measuring green economy transition in Bogor Regency. Using a composite index methodology adopted from OECD and UNDP best practices, the GEI integrates 15 indicators across three pillars: economic (6 indicators), social (4 indicators), and environmental (5 indicators). Data were collected from official government publications (BPS, KLHK) for the period 2020-2024. The index was constructed using min-max normalization and geometric mean aggregation. Model validation through backtesting showed a Mean Absolute Percentage Error (MAPE) of 5.10%, classified as "Highly Accurate." Results indicate that Bogor Regency's GEI reached 50.16 in 2024 ("Moderate" category), with the Social Pillar performing best (62.49), followed by Environmental (50.46) and Economic (40.03). Scenario projections suggest the GEI could reach 61.76 by 2030 under moderate assumptions (CAGR 3.53%). This study provides an evidence-based framework for green economy policy formulation at the regional level.